Directory of technical/vocational training programmes in tertiary level institutions of the Organisation of Eastern Caribbean States and The British Virgin Islands - Barnett, Alvin F. E. (Office of University Services, 1990)
This directory attempts to include all programmes aimed at supplying the necessary knowledge and skills for specific occupations. The programmes listed fall into one or another of the following broad categories: agriculture, construction and engineering technology, business and commercial studies, health sciences, and hospitality studies. It provides the following information for each training institution. 1) name, address, and telephone number; 2) general policies with regard to training; 3) training programmes and their courses; 4) normal class size and frequency of intake; 5) programme and course duration; 6) application procedures; 7) conditions of study; 8) examinations; 9) certification; and 10) regulatory bodies with responsibility for registration of workers.
Keywords: Technical education